1988
DOI: 10.1071/bi9880103
|View full text |Cite
|
Sign up to set email alerts
|

Current Topics in Artificial Insemination of Sheep

Abstract: There have been developments in several aspects of artificial insemination (AI) in recent years, some of which have been directly responsible for proliferation of AI in the sheep-breeding industries of several countries. The most notable advances have probably been associated with the development of intrauterine insemination by laparoscopy. There is potential for refinement of some of the related techniques, particularly in the area of control of ovulation and definition of appropriate times and optimum doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…However, the critical threshold may be reached at different total numbers of spermatozoa depending on the semen freezing method. Evans (1988) also suggested that, in the ewe, additional investigations need to be undertaken under various conditions to determine the minimum dose of motile spermatozoa to maintain fertility rates.…”
Section: Resultsmentioning
confidence: 99%
“…However, the critical threshold may be reached at different total numbers of spermatozoa depending on the semen freezing method. Evans (1988) also suggested that, in the ewe, additional investigations need to be undertaken under various conditions to determine the minimum dose of motile spermatozoa to maintain fertility rates.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the fundamentals of cryoinjury in spermatozoa is now being undertaken, and is reviewed in this article. The aim of this review is not to provide an exhaustive account of the cryopreservation of spermatozoa species by species; that has been done in several reviews recently (Amann and Pickett 1987;Evans 1988;Watson 1990;Bwanga 1991;Klug et al 1992). Rather, it will attempt to present the author's perspective on the subject, emphasizing those areas of development in which it is considered the most useful progress is being made, or could be made if resources were devoted to those aspects.…”
Section: Introductionmentioning
confidence: 98%
“…The preservation of sperm generally requires a reduction or arrest of the metabolism of sperm cells, and thereby, prolongs their fertile life [39,59]. Cryopreservation produces cold shock and oxidative attack on the sperm membrane, both of which decrease the survival and fertilizing ability of sperm, and thus, lead to sperm death and a negative impact on the preservation of semen for AI [27,38]. The cold shock of spermatozoa is partly associated with oxidative attack and the generation of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%